2017
DOI: 10.1140/epjc/s10052-017-4782-0
|View full text |Cite
|
Sign up to set email alerts
|

Radial excitations of the decuplet baryons

Abstract: The ground and first excited states of the decuplet baryons are studied using the two-point QCD sum rule approach. The mass and residue of these states are computed and compared with the existing experimental data and other theoretical predictions. The results for the masses of the ground state particles as well as the excited and * states are in good consistency with experimental data. Our results on the excited * and − states reveal that the experimentally poorly known (1950) and − (2250) can be assigned to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
(43 reference statements)
3
19
0
Order By: Relevance
“…Because, the current η(x) couples not only to states c and c , but also to − c , in the physical side of the sum rule we explicitly take into account their contributions by adopting the "groundstate+first orbitally+first radially excited states+continuum" scheme: We follow an approach applied recently to a calculation of the masses and residues of radially excited octet and decuplet baryons in Refs. [50,51]. In this work the authors got results which are compatible with existing experimental data on the masses of the radially excited baryons, and they demonstrated that besides ground-state baryons the QCD sum rule method can be successfully applied to the investigation of their excitations as well.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Because, the current η(x) couples not only to states c and c , but also to − c , in the physical side of the sum rule we explicitly take into account their contributions by adopting the "groundstate+first orbitally+first radially excited states+continuum" scheme: We follow an approach applied recently to a calculation of the masses and residues of radially excited octet and decuplet baryons in Refs. [50,51]. In this work the authors got results which are compatible with existing experimental data on the masses of the radially excited baryons, and they demonstrated that besides ground-state baryons the QCD sum rule method can be successfully applied to the investigation of their excitations as well.…”
Section: Introductionsupporting
confidence: 83%
“…Their undesired effects can be eliminated by applying a special ordering of the Dirac matrices (see for example Ref. [50]). It is not difficult to demonstrate that the structures ∼ / pg μν and ∼g μν are free of contaminations and formed only due to contributions of spin-3/2 baryons.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the prediction given by Ref. [19] is 2176 AE 219 MeV obtained using the QCD sum rule method. If we consider the central value of this result, it is larger than the observed mass of Ωð2012Þ.…”
mentioning
confidence: 84%
“…Its strong decay was studied recently in [15], using the chiral quark model, and as a result, the possibility of Ωð2012Þ being J P ¼ 3=2 − was underlined; however, it also stated that the results obtained for the possibility of it being J P ¼ 1=2 − or J P ¼ 3=2 þ are consistent with the results of the Belle Collaboration within the uncertainties. There are also some studies on the radiative decays [16] and magnetic moments of negative parity baryons [17,18].References [3,19] present the predictions on the mass of radially excited decuplet baryons. The prediction of [3] for the 2S state is 2065 MeV and it is close to the mass of Ωð2012Þ.…”
mentioning
confidence: 99%
“…In various models and methods, such as the Skyrme model [3], quark model [4][5][6][7][8][9][10][11][12][13], lattice gauge theory [14,15] and so on [16][17][18][19][20][21], the masses of the first orbital excitations of Ωð1672Þ are predicted to be ∼2.0 GeV. Thus, the newly observed Ωð2012Þ may be a good candidate for the first orbital (1P) excitations of Ωð1672Þ.…”
Section: Introductionmentioning
confidence: 99%